Solution processed transition metal oxides selective contacts for Si heterojunction solar cells - Lu, Chenjin (Nanyang Technological University, 2021)
Photovoltaics (PV) plays an increasingly important role as renewable energy to lower the carbon footprint and meet the world’s energy demand owing to its abundance. Silicon (Si) PV, attributed to its material abundance and processing experience leveraged from CMOS industry, dominates the PV market. Si heterojunctions cells, represented by heterojunction with intrinsic thin layer (HIT) technology, enable higher performance and lower fabrications cost, which has demonstrated the world champion efficiency of 26.7%. However, the p-type amorphous Si (a-Si) layer in this configuration suffers from parasitic absorption and high recombination. Therefore, alternatives materials, such as transition metal oxides (TMOs), with carrier selectivity similar to p-type a-Si that can improve current performance have attracted strong research interest. TMOs, such as MoO3, V2O5 and WO3 are originally applied in organic electronics as hole transport layers. TMOs, usually having large bandgap greater than 3 eV and are able to be processed at low temperature and are of low cost as a-Si. Most importantly, high theoretical work-function greater than 6.0 eV, are promising candidates to create an inversion layer at the n type Si (n-Si) surface resulting in an induced p-n junction for carrier separation as it is in Si heterojunction solar cell (HSCs). Most importantly, the carrier selectivity of TMOs is believed to be originated from oxygen vacancies related traps, through which carriers are extracted or transported through trap assisted tunnelling across the TMO and Si heterojunction. It has been reported that TMO/a-Si(i)/n-Si HSCs passivated with an a-Si:H layer have efficiency of 22.5 % with improved current performance, which is comparable to typical HIT cells with configuration of a-Si(p)/a-Si(i)/n-Si. Meanwhile, TMOs have demonstrated good passivation on Si, and thus simpler device configuration has been proposed without the a-Si(i) passivation layer. Such planar TMO/n-Si HSCs, embodied by MoOx/n-Si, V2Ox/n-Si and WOx/n-Si, have demonstrated the best efficiency of above 15.3%, and 15.7% and 12.5% respectively. It is noted that those reported TMOs/Si cells are based on thermal evaporation process for the deposition of the TMO layers, which requires expensive instruments and vacuum chamber. We have proposed to prepare TMO layers using sol-gel solution process. The obvious advantages are its fast, non-vacuum and room temperature process, and its potential for mass production. So far, HSCs based on solution processed TMOs (s-TMOs) on n-Si are not widely studied. In this work, we have first prepared hole selective contacts using solution processed MoOx (s-MoOx) by spin-coating and physical evaporated MoOx (e-MoOx) by electron beam evaporator. The performance of the s-MoOx/Si HSC has been investigated and optimized, which has been demonstrated solar cell efficiency of 12.5% for s-MoOx/Si HSC that is comparable to efficiency of 13.3% for e-MoOx/Si HSC. The performance of s-MoOx/Si HSC, to the best of our knowledge, is the highest among all solution processed TMO/Si HSCs and it is approaching others reported on e-MoOx/Si HSC. The slightly lower performance is mainly attributed to the slightly smaller open circuit voltage (Voc) and fill factor (FF) in the s-MoOx/Si HSCs. The investigation has shown that the slightly better performance in Voc and FF in e-MoOx/Si HSC is owing to the better carrier selectivity of 11.5 for e-MoOx film on Si in comparison to 10.1 for s-MoOx on Si. It is found that the lower carrier selectivity of s-MoOx on Si is due to the larger contact resistivity, but its contact recombination current density is better than e-MoOx on Si. The difference in the contact resistivity is believed to be associated with the trap profiles in the MoOx layer. Overall, this study has demonstrated the potentials to employ fast and convenient solution processed MoOx for Si HSCs with good cell performance. On the other hand, solution processed s-V2Ox and s-WOx thin films have been also investigated in terms of their material properties and applications in Si HSCs. The highest power conversion efficiency (PCE) of the planar for s-V2Ox/Si HSCs and s-WOx/Si HSCs after optimization is 10.8%, and 9.3% respectively. To best of our knowledge, the PCE of our planar s-V2Ox/Si HSCs is higher than other reported for solution processed s-V2Ox and the investigation and the performance for s-WOx/Si HSCs is the first reported. The performance of the s-WOx/Si HSCs lower owing to the smaller Voc because of the lower work function of only 4.71 eV in the s-WOx thin films. While there is the s-shape J-V characteristics overserved for s-V2Ox/Si HSCs lowering device FF, which is believed to be related to the energy distribution of the traps in the s-V2Ox thin films that is not favourable for trap-assisted tunnelling. The carrier selectivity of s-V2Ox and s-WOx contacts on Si was characterized, in which a lower selectivity of 8.06 was deduced for s-V2Ox and it is undetermined for s-WOx probably attributed to its weak inversion at the Si surface.